How do students understand biological concepts? A study on science literacy in basic education - Dian Arisandy Eka Putra Sembiring; Muhammad Yusuf (Jurnal Sinar Edukasi, 2025)
This analysis investigates how students in basic education comprehend biological concepts, examining cognitive processes and pedagogical factors shaping science literacy development. Drawing on contemporary research, this study analyzes mechanisms through which elementary and junior secondary students construct understanding of fundamental biological principles including cellular processes, heredity, ecosystems, and human physiology. The analysis reveals that students' comprehension operates through complex interactions between prior knowledge, developmental readiness, and instructional experiences. Research demonstrates that learners frequently maintain persistent misconceptions regarding biological phenomena, rooted in intuitive reasoning and everyday observations conflicting with scientific explanations. These alternative conceptions prove resistant to traditional instruction, necessitating conceptual change pedagogies explicitly addressing cognitive conflicts. The study identifies inquiry-based learning, hands-on experimentation, and culturally responsive instruction as particularly effective for facilitating robust understanding. Furthermore, authentic science literacy encompasses not merely factual knowledge but critical thinking competencies and abilities to apply biological concepts in analyzing real-world issues. Challenges emerge in linguistically diverse contexts where students navigate science instruction in second languages while reconciling scientific concepts with indigenous knowledge systems. This analysis concludes that enhancing biological concept comprehension requires pedagogical innovations systematically addressing misconceptions, leveraging experiential knowledge, integrating culturally relevant contexts, and cultivating higher-order cognitive capabilities essential for scientifically literate citizenship.